Pelatihan Pencatatan Data Lapangan Bidang Geoteknik untuk Peningkatan Kerapian Dokumentasi - Dwijayani, Ni Made (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
The problem faced by partners is that data recording in the field still uses paper and has the potential for damage due to weather conditions in the field. In addition, there is no special officer assigned to record data in the field. To overcome this problem, it is necessary to create a computer-based data recording format. To achieve this, training and mentoring of Ms. Excel for field officers. This activity begins with outreach to partners and jointly looking for priority problems along with their solutions. After agreeing on a solution, the proposing team prepares training materials and conducts training and mentoring. This service activity ends with carrying out an evaluation where partners already have a systematic recording of data results.